The Distributional Consequences of Rent Seeking - Angelos Angelopoulos; Konstantinos Angelopoulos; Spyridon Lazarakis; Apostolis Philippopoulos (Center for Economic Studies and ifo Institute (CESifo), 2019)
Rent seeking leads to a misallocation of resources that worsens economic outcomes and reduces aggregate welfare. We conduct a quantitative examination of the distributional effects of rent extraction via the financial sector. Rent seeking introduces a possibility for insurance against idiosyncratic earnings risk that is more valuable for poorer households that are lacking in means of self insurance. However, it also creates a wedge that discourages savings, thus reducing self insurance via asset accumulation. When the model is calibrated to US data, the distorting effects dominate, implying welfare losses for all households, and an increase in wealth inequality. Nevertheless, welfare losses are bigger for households with higher initial wealth. Therefore, a policy reform to reduce rent seeking via the financial sector, despite being Pareto improving, will benefit predominantly wealthier households.
Keywords: E02; D31; H10; 330; conditional welfare changes; wealth distribution; rent seeking